Quality of life of family carers of persons with young-onset compared to late-onset dementia. (1st September 2020) - Hvidsten, Lara; Engedal, Knut; Selbaek, Geir; Wyller, Torgeir Bruun; Šaltytė Benth, Jūratė; Bruvik, Frøydis; Kersten, Hege
Abstract: Objectives: To compare quality of life (QOL) of family carers of persons with young- (YOD) to late-onset dementia (LOD). Methods: This was a cross-sectional comparison of 88 carers of persons with YOD and 100 carers of persons with LOD. The Quality of Life – Alzheimer's Disease questionnaire (QOL–AD) was used to measure QOL of both carers and persons with dementia. Depressive symptoms were measured by the Geriatric Depression Scale (GDS) for carers and the Cornell Scale for Depression in Dementia for persons with dementia. Care burden was measured by the Relatives' Stress Scale. Activities of Daily Living (ADL) of the persons with dementia were assessed using the total score from the Lawton & Brody Instrumental-ADL scale and the Physical Self-Maintenance Scale. Multiple linear regression models with interactions between covariates and group (YOD versus LOD) were estimated. Results: The QOL–AD scores of YOD-carers were significantly poorer compared to LOD-carers (mean difference 2.5 (95% CI 0.7; 4.3), p  = 0.006). Poorer QOL of carers was associated with more depressive symptoms (mean QOL-AD change −0.5 (−0.6; −0.3), p  < 0.001), but with no difference between the two groups. In contrast to LOD, QOL of carers of people with YOD was also significantly associated with symptom duration ( p  = 0.002), depressive symptoms of the persons with dementia ( p  = 0.030), ADL ( p  = 0.001), and carer burden ( p  = 0.002). Conclusion: YOD-carers reported significantly poorer QOL compared to LOD-carers. QOL was significantly associated with depressive symptoms in carers of both groups.